Genetic Association of Hematopoietic Stem Cell Transplantation Outcome beyond Histocompatibility Genes - Gam, Rihab; Shah, Pranali; Crossland, Rachel E.; Norden, Jean; Dickinson, Anne M.; Dressel, Ralf (Frontiers in Immunology, 2017)
The outcome of hematopoietic stem cell transplantation (HSCT) is controlled by genetic factors among which the leukocyte antigen (HLA) matching is most important. In addition, minor histocompatibility antigens (miHAg) and non-HLA gene polymorphisms in genes controlling immune responses are known to contribute to the risks associated with HSCT. Besides single nucleotide polymorphisms (SNP) in protein coding genes, SNP in regulatory elements such as microRNAs (miRNA) contribute to these genetic risks. However, genetic risks require for their realization the expression of the respective gene or miRNA. Thus, gene and miRNA expression studies may help to identify genes and SNPs that indeed affect the outcome of HSCT. In this review, we summarize gene expression profiling studies that were performed in recent years in both patients and animal models to identify genes regulated during HSCT. We discuss SNP-mRNA-miRNA regulatory networks and their contribution to the risks associated with HSCT in specific examples, including FOXP3 and regulatory T cells, the role of the miR-155 and miR-146a regulatory network for graft versus host disease, and the function of MICA and its receptor NKG2D for the outcome of HSCT. These examples demonstrate how SNPs affect expression or function of proteins that modulate the alloimmune response and influence the outcome of HSCT. Specific miRNAs targeting these genes and directly affecting expression of mRNAs are identified. It might be valuable in the future to determine SNPs and to analyse miRNA and mRNA expression in parallel in cohorts of HSCT patients to further elucidate genetic risks of HSCT.